DIACHRONIC AND SYNCHRONIC ASPECTS OF FORMS OF ADDRESS - Javlieva Guljakhon Murodovna (Bright Mind Publishing, 2025)
This article analyzes the socio- linguistic features of forms of address, focusing especially on how they relate to occupation, age, and gender. Forms of address reflect not only the communicative function of language but also convey social roles, standards of respect, and professional hierarchy within a community (Brown & Levinson, 1987; Bondaletov, 1987).
Keywords: Forms of address, sociolinguistics, occupation, age, gender, social role.